Zao Ren An Shen capsule for insomnia: a double-blind, randomized, placebo-controlled trial. Issue 2 (12th November 2021) - Birling, Yoann; Zhu, Xiaoshu; Avard, Nicole; Tannous, Caterina; Fahey, Paul P; Sarris, Jerome; Bensoussan, Alan
Abstract: Study Objectives: The aim of this study was to test the efficacy and safety of Zao Ren An Shen (ZRAS) capsule, a Chinese herbal medicine product, for the treatment of insomnia. Methods: We conducted a double-blind randomized placebo-controlled trial. After a one-week placebo run-in, a total of 85 people with insomnia were randomly allocated to receive ZRAS or placebo for 4 weeks. The primary outcomes were insomnia severity assessed with the Insomnia Severity Index (ISI) and the number of participants with adverse events (AEs). Secondary outcomes included objective and subjective sleep parameters, psychological status, fatigue level, quality of life, acceptability, and tolerability. Results: A nonsignificant ( p > .05) difference of 0.7 points in ISI in favor of ZRAS capsule was found at the end of the treatment. The number of participants with AEs was not significantly different ( p > .05) between the two groups. Except for subjective sleep onset latency, which had a nonsignificant ( p > .05) medium effect (Cohen's d = 0.5), the effects in secondary efficacy outcomes were all small (Cohen's d < .4) and nonsignificant ( p > .05). The acceptability and tolerability were high in the active group. Conclusions: ZRAS capsule is safe, acceptable, and tolerable, yet not more effective than placebo in the treatment of insomnia. As previous evidence showed that Chinese herbal medicine was effective for insomnia, these results may be explained by the dose of the product, which was lower than the dose generally used in the clinic. Registration: This clinical trial was registered in Australia New Zealand Clinical Trial Registry (registration number ACTRN12619000140156) under the name "Impact of Zao Ren An Shen (ZRAS) capsule on chronic insomnia patients' insomnia severity: A randomized-controlled trial" (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=376730&isReview=true ).